Barriers to energy-efficiency implementation: a study of the uptake of energy-efficiency initiatives offered through incentive schemes in South Africa - Parker, Victoria Daniela (Energy Research Centre, 2017)
Energy efficiency has been widely recognised as a powerful tool for improving the energy situation across the globe. Whether by increasing energy security, reducing carbon emissions or alleviating grid strain, proven methods of energyefficiency management can bring about significant savings at a multitude of levels. Although energy-efficiency practices are gaining traction globally, their uptake is still less than optimal, and this is especially true of South Africa. The country is currently facing an energy crisis that brings with it a variety of complex challenges, all which can be assuaged through energy efficiency, if applied to the energy-intensive economy. It is important to understand the South Africa-specific barriers that hinder implementation of energy efficiency. While government has made strong commitments to supporting the uptake of energy-efficiency initiatives, there have been several interruptions and a lack of execution. An abundant amount of topdown research has been conducted to identify the various barriers to implementation; far less research, however, identifies barriers from within these energy-intensive economies. If these barriers could be identified from a more qualitative and participant-centred perspective, the key role-players in the sector might be able to better address energy-efficiency implementation, leading to more widespread benefits and results. To this end, the researcher performed an explanatory investigation, analysing seven energy-intensive companies that had recently participated in a fully funded local incentive scheme called the Private Sector Energy Efficiency Programme (PSEE). The PSEE performed an energy audit on each company, followed up by a report on its findings. The report clearly outlined the company's key energy-savings opportunities, in kilowatt-hours (kWh), Rand and CO2 emissions. It also estimated the costs and payback periods of the projects. Despite these reports indicating significant savings potentials and reasonable payback periods, a lack of uptake still remained. The researcher extracted and analysed the relevant quantitative data from the PSEE reports and conducted one-on-one, semi-structured interviews with the participants to identify and understand the participant-specific barriers to the recommended energy-efficient measures. The researcher also interviewed three coordinators of the PSEE programme, in the hope of identifying any PSEEspecific barriers. The other main party involved in this research was PSEE energy-efficiency ESCO which has been given an alias name ESCO E, who delivered the reports to the participants. The research found that the barriers in place in South Africa resemble those that have been identified at the global level. However, the mixed-methods approach and data sample employed in this study create a very interesting picture about the barriers that exist at the company level. The research found that there were significant saving opportunities available to companies but that, mainly due to a lack of financial support, human-resource capacity and time, there has been little to no implementation of the recommended projects. The available literature and provided global experience, coupled with participants' responses and suggestions, allow the researcher to make relevant recommendations that pertain to the study: • Lower payback periods through further incentives • Accessible funding and subsidies • Ensured continuation, longevity and growth of incentive programmes • Client-specific cost alternatives • Extensive and supported detail around each recommendation • Human resource capacity support to ensure energy management • Required energy seminars and skills training to programme participants • Increased government support and energy efficiency resources; namely an Energy Hub, which will provide a stable platform for energy efficiency • Participant-specific report alignment to encourage uptake and increased trust between incentive host and participant • More stringent government regulated technological standards.